MUC1: A multifunctional cell surface component of reproductive tissue epithelia - Thathiah Amantha; Brayman Melissa; Carson Daniel D (BMC, 2004)
Abstract MUC1 is a large, transmembrane mucin glycoprotein expressed at the apical surface of a variety of reproductive tract epithelia. Functions attributed to MUC1 include those generally associated with mucins such as lubrication and hydration of cell surfaces as well as protection from microorganisms and degradative enzymes. In addition, MUC1 is an effective inhibitor of both cell-cell and cell-extracellular matrix interactions in both normal and malignant contexts. Moreover, a series of recent studies has shown that the highly conserved cytoplasmic tail of MUC1 interacts specifically with a series of important signal transducing molecules including β-catenin, Grb2 and erbB family members. MUC1 expression in normal epithelia can be quite dynamic, varying in response to steroid hormone or cytokine influences. Following malignant transformation, MUC1 often becomes highly overexpressed, loses its apical restriction, and displays aberrant glycosylation and altered mRNA splice variants. Regulation of MUC1 expression can occur at the transcriptional level. In addition, post-translational regulation of cell surface expression occurs via the activity of cell surface proteases or "sheddases" that release soluble forms of the large ectodomains. This review will briefly summarize studies of MUC1 expression and function in reproductive tissues with particular emphasis on the uterus. In addition, current knowledge of the mechanisms of MUC1 gene regulation, metabolic processing and potential signal transducing functions will be presented.